Comparison of caffeine contents in dark chocolate and white chocolate using high performance liquid chromatography (HPLC) / Nur Tiara Abd Halim - Abd Halim, Nur Tiara (2017)
This study was conducted to compare the amount of caffeine in two types of chocolate from two difference brands. Caffeine were extracted from dark chocolate and white chocolate samples by using liquid-liquid extraction (LLE) method and chloroform as extracting agent. Then, the concentration level of caffeine was determined by using high performance liquid chromatography (HPLC). The calibration curve of standard solutions showed linearity of y = 420.41x + 14.565 and R2 = 0.09978. The data shows that dark chocolates from Brand A and Brand B contain 0.034 mg/g and 0.035 mg/g of caffeine contents respectively, while white chocolate from both brands contain 0.002 mg/g of caffeine contents. Since all chocolate samples contain caffeine lower than a maximum value recommended by regulations which is 1.25 mg/g so, chocolate samples used in this analysis can safely consumed by all generations.